Study guides

☆☆

Q: How do you factor x2 plus 13x plus 36?

Write your answer...

Submit

Still have questions?

Related questions

x2 + 13x + 36 = (x + 9)(x + 4)

The factors of x2-13x+36 are 'x-9' and 'x-4'because the expression (x-9)(x-4) can be simplified as x2-13x+36.

(x-4)

(x + 4)(x + 9)

(x-4)(x-9)

x2-13x+36 = (x-4)(x-9) when factored

x2-13x+12 = (x-1)(x-12) when factored

vbh

x2 + 13x + 36 = 0 so (x+4)(x+9) = 0 so that x = -4 or x = -9

x2-13x+36=(x-9)(x-4)=0 x=9 or x=4

If that's plus 36, it factors to (x - 9)(x - 4) If it's minus 36, it gets ugly in a hurry.

(x - 9)(x - 4)

(x + 10)(x + 3)

(x - 10)(x - 3)

x2 + 13x + 12 = (x + 1)(x + 12)

x2 + 13x + 40 = x2 + 5x + 8x + 40 = x(x + 5) + 8(x + 5) = (x + 8)(x + 5)

(x - 10)(x - 3)

(x - 5)(x - 8)

If that's -13x, the answer is (x - 10)(x - 3) If that's +13x, the answer is (x + 10)(x + 3)

(x - 6)(x - 7)

x2 + 13x = -30 ∴ x2 + 13x + 30 = 0 ∴ (x + 3)(x + 10) = 0 ∴ x ∈ {-3, -10}

x-4 is the correct answer for Apex

(x + 5)(x + 8)

x(x2 + 36)

X^2 - 13X + 30 = 0 (X-3)(X-10) easy inspection problem